The Success Case Method: A Simple Evaluation Tool to Identify Critical Success Factors and Program Impa - and Bell, Catherine; McDonalds, Diane (Australian Evaluation Society Inc., 2006)
Identification and reporting of critical success factors and program impact in an efficient, yet comprehensive manner is an inherent difficulty facing many evaluators of large-scale evaluations. This paper details how two evaluators encountered such problems in the initial review of a large-scale initiative and then successfully addressed these issues through the application of the Success Case Method in a subsequent evaluation of the same program. The Success Case Method is a down-to-earth evaluation tool that can be used for: finding out what is working and what is not, which also provides accurate and trustworthy information that can be used to make timely decisions (Brinkerhoff, 2003, p.3). This paper reports on the advantages of applying this approach to the evaluation of the Primary Welfare Officer Initiative (PWOI), a program that aims to improve the capacity of schools to support students at risk of disengagement and who are not achieving their educational potential.